Tigecycline in the treatment of severe pneumonia caused by Chlamydia psittaci: A case report and literature review - Liu, Jiaming; Gao, Yuan (Frontiers in Medicine, 2022)
Psittacosis is a zoonotic disease caused by Chlamydia psittaci. Systemic infections are mainly transmitted through the respiratory tract. The most common related disease is human atypical pneumonia, which is a rare pathogen of community-acquired pneumonia. Due to the difficulty of diagnosis, there have been few reports of Chlamydia psittaci pneumonia in the past. In recent years, with the widespread application of mNGS (metagenomic next-generation sequencing), the number of reported cases of Chlamydia psittaci has increased year by year. However, at present, most hospitals have little understanding of Chlamydia psittaci, especially for severe patients, and lack experience in diagnosis and treatment. Herein, we report the case of a 71-year-old woman with severe pneumonia that caused by Chlamydia psittaci. This patient was diagnosed through mNGS and was treated with tigecycline successfully. The level of IL-6 in the BALF was significantly increased. We discontinued tigecycline after mNGS of the blood was negative. In this review, we analyzed 23 cases to summarize the etiology, clinical manifestations, diagnosis and treatment strategies of severe Chlamydia psittaci pneumonia and hope to raise clinicians’ awareness of this disease.